The Use of Turmeric Extract (Curcuma domestica) for the Treatment and Survival of Comet Fish (Carassius auratus auratus) Infected with Aeromonas hydrophila Bacteria - Utiya, Tri Yuningsih P; Tuiyo, Rully; Lamadi, Arafik (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Comet fish (Carassius auratus auratus) is one type of freshwater ornamental fish that is highly demanded by the ornamental fish hobbyist community because it has a variety of colors and attractive physical forms. However, comet fish cultivation has decreased due to disease attacks that lead to death caused by Aeromonas hydrophila bacteria. Therefore, farmers generally use chemical drugs such as antibiotics to treat diseases in comet fish, yet for antibiotics, and it is necessary to research herbal medicines that contain antibacterial content, such as turmeric (Curcuma domestica). This research aims to determine the effect of immersion time using turmeric extract solution for treatment and survival rate of comet fish seeds infected with A.hydrophila bacteria. This is experimental research with a Completely Randomized Design (CRD) consisting of four treatments and three replicates, namely treatment A (control), B (50 minutes immersion), C (60 minutes immersion), and D (70 minutes immersion). The results showed that using turmeric extract affected treating comet fish seeds infected with A.hydrophila bacteria. As for the survival rate, the results of analysis of variance (ANOVA) showed that the use of turmeric extract had no significant effect, with the percentage value of the survival rate of comet fish seeds of treatment A (63.30%), B (90.00%), C (80.00%), and D (86.60%).